HAMBATAN KOMUNIKASI ANTARA APARAT POLISI DENGAN ALIANSI MAHASISWA PAPUA (AMP) SURABAYA - Ade Safri Simanjuntak (Kanal: Jurnal Ilmu Komunikasi, 2015)
This research aimed to describe rallies Papua Students Alliance and analyze of communication barriers between police with Papua students alliance Surabaya on demonstrations addressing violence shootings Indonesian military in Papua that sparked mass unrest. Data was collected by in-depth interviews; direct observation (passive participation), and documents. The results showed that the main factors that often lead to anarchy mass in certain circumstances were the police officers that were involved to secure it. It was Indicated tactics and strategies that were adopted by the police which could spark violence, when they used the threat, warning or limiting of protesters space. Police used physical violence (like a slap in the face), which later gave birth to a chain effect. Protesters and police failed to conduct dialogic communication that caused the riot in the demonstrations carried out. These conditions were communication barriers that indicated weaknesses in the police procedural safeguards.